Osteoprotective Effects in Postmenopausal Osteoporosis Rat Model: Oral Tocotrienol vs. Intraosseous Injection of Tocotrienol-Poly Lactic-Co-Glycolic Acid Combination - Ibrahim, Nurul ‘Izzah; Mohd Noor, Hasnul ‘Iffah; Shuid, Ahmad Naqib; Mohamad, Sharlina; Abdul Malik, Mohd Maaruf; Jayusman, Putri Ayu; Shuid, Ahmad Nazrun; Naina Mohamed, Isa (Frontiers in Pharmacology, 2021)
Osteoporosis, the most common bone disease, is associated with compromised bone strength and increased risk of fracture. Previous studies have shown that oxidative stress contributes to the progression of osteoporosis. Specifically, for post-menopausal osteoporosis, the reduction in oestrogen levels leads to increased oxidative stress in bone remodelling. Tocotrienol, a member of vitamin E that exhibits antioxidant activities, has shown potential as agent for treatment of osteoporosis. Most studies on the osteoprotective effects of tocotrienols had used the oral form of tocotrienols, despite their low bioavailability due the lack of transfer proteins and high metabolism in the liver. Several bone studies have utilised tocotrienol combined with a nanocarrier to produce a controlled release of tocotrienol particles into the system. However, the potential of delivering tocotrienol-nanocarrier combination through the intraosseous route has never been explored. In this study, tocotrienol was combined with a nanocarrier, Poly Lactic-co-Glycolic Acid (PLGA) and injected intraosseously into the bones of ovariectomised rats to produce targeted and controlled delivery of tocotrienol into the bone microenvironment. This new form of tocotrienol delivery was compared to the conventional oral delivery in terms of their effects on the bone parameters. Forty Sprague Dawley rats were divided into five groups. The first group was sham-operated (SO), while other groups were ovariectomized (OVX). Following two months, the right tibiae of all the rats were drilled at metaphysis region to provide access for intraosseous injection. The estrogen group (OVX+ESTO) and tocotrienol group (OVX+ TTO) were given daily oral gavages of Premarin (64.5 mg/kg) and annatto-tocotrienol (60 mg/kg), respectively. The locally administered tocotrienol group (OVX+TTL) was given a single intraosseous injection of tocotrienol-PLGA combination. After 8 weeks of treatment, the bone parameters measured were biochemical markers, micro-CT, DEXA and biomechanical test. Based on the results of most of the parameters, the OVX+ TTO or OVX+TTL groups offered bone protective effects with similar trends to the positive control group (OVX+ESTO). There were no significant differences between OVX+TTO and OVX+TTL groups. In conclusion, daily oral tocotrienol and one-time intraosseous injection of tocotrienol-PLGA combination were equally effective in protection against ovariectomy-induced bone changes.